Structural basis for human NADPH-cytochrome P450 oxidoreductase deficiency - Xia, Chuanwu (National Academy of Sciences, 2011)
NADPH-cytochrome P450 oxidoreductase (CYPOR) is essential for electron donation to microsomal cytochrome P450-mediated monooxygenation in such diverse physiological processes as drug metabolism (approximately 85–90% of therapeutic drugs), steroid biosynthesis, and bioactive metabolite production (vitamin D and retinoic acid metabolites). Expressed by a single gene, CYPOR’s role with these multiple redox partners renders it a model for understanding protein–protein interactions at the structural level. Polymorphisms in human CYPOR have been shown to lead to defects in bone development and steroidogenesis, resulting in sexual dimorphisms, the severity of which differs significantly depending on the degree of CYPOR impairment. The atomic structure of human CYPOR is presented, with structures of two naturally occurring missense mutations, V492E and R457H. The overall structures of these CYPOR variants are similar to wild type. However, in both variants, local disruption of H bonding and salt bridging, involving the FAD pyrophosphate moiety, leads to weaker FAD binding, unstable protein, and loss of catalytic activity, which can be rescued by cofactor addition. The modes of polypeptide unfolding in these two variants differ significantly, as revealed by limited trypsin digestion: V492E is less stable but unfolds locally and gradually, whereas R457H is more stable but unfolds globally. FAD addition to either variant prevents trypsin digestion, supporting the role of the cofactor in conferring stability to CYPOR structure. Thus, CYPOR dysfunction in patients harboring these particular mutations may possibly be prevented by riboflavin therapy in utero, if predicted prenatally, or rescued postnatally in less severe cases.